Analysis of Emergency Medical Rescue in the "8–12" Tianjin Port Heavy Fire Explosion Accident. Issue 2 (5th April 2021) - Dong, Wenlong; Jin, Jie; Lu, Ming; Ding, Hui; Lv, Qi; Fan, Haojun; Hou, Shike; Fan, Bin
Abstract: With the progress in science and technology, hazardous chemicals are becoming more essential in chemical products, industrial and agricultural production, and daily life. Hazardous chemicals have poisoning, corrosive, explosive, and combusting natures; once on fire, they can trigger a chain of catastrophic incidences, resulting in casualties, property loss, and environmental pollution and posing hazards to life and property. Using the "8–12" explosion of the Ruihai Logistics warehouse in Tianjin Port (Binhai New District, China), the present study analyzes the characteristics of trauma of the casualties in this accident and the emergency medical rescue strategies. The goals were to improve the ability of emergency rescue in such accidents and to save people's lives and property to the maximum extent.